Historical avant-garde, science, and philosophy (Philology, 2026)
The article presents the phenomenon “historical avant-garde” in its European forms and Bulgarian manifestations, its conceptual and aesthetic peculiarities, as well as the scientific and philosophical foundations underlying it. It continues the relationship between the main scientific and philosophical ideas of the times and their importance in forming the cardinal conceptual views and aesthetic perceptions of the avant-garde, as well as their influence on the construction of the visual system of the actual avant-garde art between the two world wars.
Keywords: avant-garde; modernism; dadaism; constructivism